Digital technologies commercially available in Germany in the context of nature conservation and ecosystem service provisioning in agriculture - Krachunova, Tsvetelina; Geppert, Frauke; Lemke, Nahleen; Bellingrath-Kimura, Sonoko D. (Frontiers in Sustainable Food Systems, 2025)
This review focused on the inventory of current digital technologies available on the agricultural market in Germany. A total of 189 digital technologies were found as of December 2023. Digital technologies in agriculture rarely contain few components. They consist of various other technologies that have many common interfaces. Therefore, a classification on two levels was done: technologies categorized according to their type (software-based and hardware-based technologies) and mode of operation (farm management information systems/ decision support systems, digital technologies for guidance and steering, digital information platforms, citizen science applications and platforms, sensors, field robots and unmanned aerial vehicles). Furthermore, the expected potentials of these digital tools for the promotion of nature conservation and ecosystem service provisioning in Germany were framed. The review also discusses barriers that can impact nature conservation and ecosystem service provisioning. Germany, as one of the world’s leading nations in the production and use of modern technologies, had set ambitious goals regarding digitalisation as a solution for nature conservation and ecosystem service provisioning problems, which have not yet been fulfilled. The potentials for nature conservation and ecosystem service provisioning are still strongly supressed by non-sustainable barriers, e.g., high acquisition costs, practical maturity, mode of operation and infrastructure. Current policies and societal preferences are not yet contributing enough to steer the use of digital technologies in a direction of nature conservation and providing ecosystem services. Furthermore, the main participants in the digitalisation discussion are researchers, whereby the smallest group of participants are farmers. For a sustainable digital transformation of agriculture, including restoration and protection targets of nature, and ecosystems, more wide-ranging, and diversifying changes supported by digitalisation are needed along agricultural and ecological concepts leading to long-term resilience of agricultural systems.